Alterations in the gut microbiome and its metabolites are associated with the immune response to mucosal immunization with Lactiplantibacillus plantarum-displaying recombinant SARS-CoV-2 spike epitopes in mice - Hwang, In-Chan; Vasquez, Robie; Song, Ji Hoon; Engstrand, Lars; Valeriano, Valerie Diane; Kang, Dae-Kyung (Frontiers in Cellular and Infection Microbiology, 2023)
Lactic acid bacteria (LAB) expressing foreign antigens have great potential as mucosal vaccines. Our previous study reported that recombinant Lactiplantibacillus plantarum SK156 displaying SARS-CoV-2 spike S1 epitopes elicited humoral and cell-mediated immune responses in mice. Here, we further examined the effect of the LAB-based mucosal vaccine on gut microbiome composition and function, and gut microbiota-derived metabolites. Forty-nine (49) female BALB/c mice were orally administered L. plantarum SK156-displaying SARS-CoV-2 spike S1 epitopes thrice (at 14-day intervals). Mucosal immunization considerably altered the gut microbiome of mice by enriching the abundance of beneficial gut bacteria, such as Muribaculaceae, Mucispirillum, Ruminococcaceae, Alistipes, Roseburia, and Clostridia vadinBB60. Moreover, the predicted function of the gut microbiome showed increased metabolic pathways for amino acids, energy, carbohydrates, cofactors, and vitamins. The fecal concentration of short-chain fatty acids, especially butyrate, was also altered by mucosal immunization. Notably, alterations in gut microbiome composition, function, and butyrate levels were positively associated with the immune response to the vaccine. Our results suggest that the gut microbiome and its metabolites may have influenced the immunogenicity of the LAB-based SARS-CoV-2 vaccine.